Advanced glycation end products are elevated in estrogen receptor-positive breast cancer patients, alter response to therapy, and can be targeted by lifestyle intervention - Walter, Katherine R.; Ford, Marvella E.; Gregoski, Mathew J.; Kramer, Rita M.; Knight, Kendrea D.; Spruill, Laura; Nogueira, Lourdes M.; Krisanits, Bradley A.; Phan, Van; La Rue, Amanda C.; Lilly, Michael B.; Ambs, Stefan; et al. (Breast cancer research and treatment, 2019)
Purpose Lifestyle factors associated with personal behavior can alter tumor-associated biological pathways and thereby increase cancer risk, growth, and disease recurrence. Advanced glycation end products (AGEs) are reactive metabolites produced endogenously as a by-product of normal metabolism. A Western lifestyle also promotes AGE accumulation in the body which is associated with disease phenotypes through modification of the genome, protein crosslinking/dysfunction, and aberrant cell signaling. Given the links between lifestyle, AGEs, and disease, we examined the association between dietary-AGEs and breast cancer. Methods We evaluated AGE levels in bio-specimens from estrogen receptor-positive (ER+) and estrogen receptor-negative (ER−) breast cancer patients, examined their role in therapy resistance, and assessed the ability of lifestyle intervention to reduce circulating AGE levels in ER+ breast cancer survivors. Results An association between ER status and AGE levels was observed in tumor and serum samples. AGE treatment of ER+ breast cancer cells altered ERα phosphorylation and promoted resistance to tamoxifen therapy. In a proof of concept study, physical activity and dietary intervention was shown to be viable options for reducing circulating AGE levels in breast cancer survivors. Conclusions There is a potential prognostic and therapeutic role for lifestyle derived AGEs in breast cancer. Given the potential benefits of lifestyle intervention on incidence and mortality, opportunities exist for the development of community health and nutritional programs aimed at reducing AGE exposure in order to improve breast cancer prevention and treatment outcomes.